Simulations of DNA denaturation dynamics under constrained conditions. (20th July 2022) - Al Qanobi, A; Marenduzzo, D; Ali, I
Abstract: We study the dynamics of double-stranded DNA (dsDNA) denaturation using Brownian dynamics simulations. We use a coarse-grained single nucleotide model for dsDNA which considers the helix structure. We compare the melting dynamics for free DNA of length 300 base pairs with that of a DNA of the same length but fixed from one end—mimicking DNA tethered to a substrate. We find that free DNA melts at faster rate because the entropic gain associated with denaturation is larger. Additionally, we insert the DNA in nanochannels of different widths to study the influence of the confinement on the melting dynamics. Our results suggest that there is no significant difference in the critical temperature or rate of melting when the channel width ⩾ R g / 2, where R g is the radius of gyration of DNA. Instead, at channel width of R g /4 we only see partial denaturation at the free DNA melting temperature. Surprisingly, this trend is reversed at higher temperature, and we find that at 110 °C tight confinement results in faster melting. This is due to the fact that confinement promotes segregation of the single-stranded segment, thereby acting as an effective entropic force aiding denaturation.